Preoperative antihypertensives and hypotension during bladder tumor resection with oral 5-aminolevulinic acid administration - Yuriko Kondo; Takahiro Mihara; Nanako Yoshikawa; Noriyuki Echigo; Yusuke Nagamine; Takahisa Goto (PLoS ONE, 2025)
5-Aminolevulinic acid hydrochloride (5-ALA), a photodynamic diagnostic agent, visualizes bladder cancer. Previous research has indicated that preoperative intake of 5-ALA leads to a higher incidence of hypotension. Particularly in patients with hypertension, suggestions include discontinuing antihypertensive medications on the morning of surgery to prevent hypotension. However, the effects of antihypertensive drugs on hypotension in patients taking 5-ALA before surgery remains unexamined. We conducted a single-center observational study that included patients aged 20 and above who were regularly taking antihypertensives and underwent transurethral resection of bladder tumors (TURBT) after taking 5-ALA. Patients who took antihypertensives on the morning of surgery were defined as the continued group, whereas those who did not were defined as the discontinued group. Hypotension was defined as a mean blood pressure (MBP) of less than 65 mmHg for 20 min or longer. To adjust for confounding factors, we used propensity scores for inverse probability weighting and performed modified Poisson regression analysis to calculate risk ratios (RRs) and 95% confidence intervals (CIs). We analyzed 132 cases. The crude incidence of hypotension was higher in the continued group compared to the discontinued group (33/51 [64.7%] vs 38/81 [46.9%]; RR 1.38, 95% CI 1.01–1.88; p =  0.041). However, no significant difference was observed between groups after adjustment (RR 1.05, 95% CI 0.66–1.68). In conclusion, the adjusted results suggested no significant association between the continuation of antihypertensive medication and the incidence of intraoperative hypotension. No substantial justification was provided for routinely discontinuing antihypertensive medications.